Yttrium oxide-aluminum oxide transition layer composite ceramic as well as preparation method and application thereof
By preparing yttrium oxide-alumina transition layer composite ceramics on alumina ceramic components, the problem of poor bonding strength of yttrium oxide coating is solved, the bonding strength and etching resistance are significantly improved, and the service life of the parts is extended.
Patent Information
- Application Number
- CN202411565504.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-05
AI Technical Summary
The bond strength of the existing yttrium oxide etch-resistant coating and substrate is poor, and the coating is prone to peeling off. High-energy fluorine-containing plasma erodes alumina ceramic components, shortening their service life.
Alumina powder, transitional mixed powder and yttrium oxide powder are laid from bottom to top in the molding mold of a cold isostatic press to form an upper layer of yttrium oxide powder, a mixture of alumina powder and yttrium oxide powder, and a lower layer of alumina oxide The structure of the powder is prepared by cold isostatic molding and high-temperature sintering process.
The bonding strength between the yttrium oxide coating and the alumina substrate is significantly improved, the protection function of the alumina substrate is enhanced, the etching resistance is improved, and the service life of alumina ceramic parts is extended.
Smart Images

Figure CN119430879A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite ceramic preparation, and in particular to an yttria-alumina transition layer composite ceramic and a preparation method and application thereof. Background Art
[0002] With the rapid development of integrated circuit technology, plasma etching technology has gradually become a widely used etching technology in nanoscale integrated circuit manufacturing and micro-nano manufacturing processes. With the increase of the energy of fluorine-containing plasma in the etching gas, high-energy fluorine-containing plasma will corrode the related alumina ceramic parts in the cavity, shortening the service life of alumina ceramic parts; at the same time, the corrosion process will generate non-volatile fluorides deposited on the wafer surface, which also increases the contamination of the wafer. Therefore, the plasma etching resistance of the related alumina ceramic parts in the etcher cavity becomes very important.
[0003] At present, yttrium oxide materials are widely used in etching-resistant coatings due to their excellent plasma etching resistance and relatively economical production costs. The bonding strength between yttrium oxide and the substrate is an important performance indicator of the etching-resistant coating. However, the existing technology often uses atmospheric plasma spraying to prepare yttrium oxide etching-resistant coatings. The bonding strength between the yttrium oxide coatings prepared by this method and the substrate is poor, and the coating is prone to peeling. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention discloses an yttria-alumina transition layer composite ceramic and a preparation method and application thereof, thereby solving or at least alleviating one or more of the above-mentioned problems and other problems in the prior art.
[0005] The present invention discloses a method for preparing an yttrium oxide-aluminum oxide transition layer composite ceramic, comprising the following steps:
[0006] S1. Raw material selection: Alumina powder and yttrium oxide powder are used;
[0007] S2. Adding a certain amount of raw materials: laying a certain amount of alumina powder, transition mixed powder and yttrium oxide powder in a molding die of a cold isostatic press from bottom to top, so as to form a raw material arrangement in which an upper layer is yttrium oxide powder, a transition layer is transition mixed powder and a lower layer is alumina powder; the transition mixed powder is a mixture of alumina powder and yttrium oxide powder;
[0008] S3, repeat step S2 n times until the raw material fills the entire molding die; wherein n ≥ 0;
[0009] S4, placing the filled molding die into a cold isostatic press for cold isostatic pressing to obtain a molded ceramic green body;
[0010] S5. Machining the formed ceramic green body to obtain at least one yttrium oxide-aluminum oxide transition layer composite ceramic green body, and machining the yttrium oxide-aluminum oxide transition layer composite ceramic green body into a designed shape, wherein the alumina portion serves as the alumina substrate, the transition mixed powder serves as the transition layer, and the yttrium oxide portion serves as the coating;
[0011] S6. The yttrium oxide-aluminum oxide transition layer composite ceramic green body obtained in step S5 is transferred to a high-temperature sintering furnace for sintering, and the yttrium oxide-aluminum oxide transition layer composite ceramic is obtained after being naturally cooled to room temperature in the furnace.
[0012] Preferably, in step S2, the laying process of the alumina powder, the transition mixed powder and the yttrium oxide powder comprises the following steps:
[0013] S201, adding alumina powder: adding a certain amount of alumina powder to a forming mold of a cold isostatic press, and vibrating and compacting the alumina powder in the forming mold;
[0014] S202, adding transition mixed powder: the transition mixed powder is a mixture of aluminum oxide powder and yttrium oxide powder; in the transition mixed powder, the mass ratio m of aluminum oxide powder and yttrium oxide powder is (3-7): (7-3); adding the transition mixed powder to a forming mold of a cold isostatic press, and vibrating and compacting the transition mixed powder in the forming mold to form a transition layer;
[0015] S203, adding yttrium oxide powder: adding a certain amount of yttrium oxide powder into a forming mold of a cold isostatic press, and vibrating and compacting the aluminum oxide powder in the forming mold.
[0016] Preferably, in step S202, the forming mold is provided with scale one and scale two near the upper and lower ends thereof, respectively, and the transition layer is located between scale one and scale two of the forming mold.
[0017] Preferably, in step S202, the thickness of the transition layer is 1 mm.
[0018] Preferably, in step 4, the cold isostatic pressing pressure is 120 MPa and the holding time is 30 s.
[0019] Preferably, in step 1, the average particle size of the aluminum oxide powder is 57 μm, and the average particle size of the yttrium oxide powder is 38 μm.
[0020] Preferably, in step 5, when n=0, the number of yttrium oxide-aluminum oxide transition layer composite ceramic green bodies obtained is 1; when n=1, the number of yttrium oxide-aluminum oxide transition layer composite ceramic green bodies obtained is 2; when n=2, the number of yttrium oxide-aluminum oxide transition layer composite ceramic green bodies obtained is 3; ... when n=n, the number of yttrium oxide-aluminum oxide transition layer composite ceramic green bodies obtained is n+1.
[0021] Preferably, in step 6, the sintering process in the high temperature sintering furnace comprises the following steps:
[0022] S601: heating up to 300°C at a rate of 200°C / h, keeping the temperature for 2h; then heating up to 400°C at a rate of 200°C / h, keeping the temperature for 2h; then heating up to 500°C at a rate of 200°C / h, keeping the temperature for 2h; then heating up to 1650°C at a rate of 200°C / h, keeping the temperature for 2h; at 300°C to 500°C, the yttrium oxide-aluminum oxide transition layer composite ceramic green body is debonded in the furnace, i.e., the binder in the yttrium oxide granulated powder and the alumina granulated powder is decomposed and discharged;
[0023] S602: The temperature is cooled from 1650°C to 1000°C at a cooling rate of 2°C / min, and then naturally cooled to room temperature along with the furnace.
[0024] Furthermore, the present invention provides yttrium oxide-aluminum oxide composite ceramics prepared by the method for preparing yttrium oxide-aluminum oxide transition layer composite ceramics as described above.
[0025] The yttria-alumina composite ceramic prepared by the present invention has excellent bonding strength, and meets the application requirements of alumina ceramic parts, especially the use requirements of alumina ceramic parts working in the inner cavity of an etcher.
[0026] In addition, the present invention also provides the use of the yttria-alumina composite ceramic as described above in the inner cavity of an etcher as an alumina ceramic component.
[0027] The present invention has the following beneficial effects:
[0028] The technical scheme provides an yttria-alumina transition layer composite ceramic and its preparation method and application. A set amount of alumina powder, transition mixed powder and yttria powder are laid in sequence from bottom to top in a forming mold of a cold isostatic press. Then, the powder raw materials in the forming mold are uniformly pressurized by a cold isostatic pressing process. The powder raw materials are compressed and the pores are discharged to obtain a formed ceramic green body with uniform structure and high density. The formed ceramic green body is then machined into a designed shape and then sintered to further improve the strength, thereby obtaining a ceramic with an alumina portion as an alumina substrate, A composite ceramic with a transition mixed powder as a transition layer and an yttrium oxide part as a coating, wherein the transition layer of the composite ceramic is a mixture of aluminum oxide powder and yttrium oxide powder, and the transition layer can reduce the gap at the interface between yttrium oxide and aluminum oxide, making the interface seamless and more compact; in addition, the aluminum oxide powder and yttrium oxide powder are evenly mixed in the transition layer, and the particles are embedded in each other, which significantly improves the mechanical locking between the materials and makes the bonding stronger; the problem of poor bonding and easy peeling of the yttrium oxide etching-resistant protective coating in the prior art is solved, and at the same time, the protective function of the aluminum oxide substrate is strengthened. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the specific embodiments of the present disclosure, the following briefly introduces the drawings required for use in the specific embodiments. In all the drawings, each element or part is not necessarily drawn according to the actual scale.
[0030] Figure 1 It is a structural schematic diagram of a forming mold in a cold isostatic press of the present invention;
[0031] Figure 2 A diagram of a ceramic green body of the present invention;
[0032] Figure 3 This is a sintered yttria-alumina transition layer composite ceramic of the present invention;
[0033] Figure 4 This is an interface morphology diagram of the yttrium oxide coating and the transition layer in the yttrium oxide-aluminum oxide composite ceramic prepared in Example 1 of the present invention;
[0034] Figure 5 This is an interface morphology diagram of the alumina substrate and the transition layer in the yttria-alumina composite ceramic prepared in Example 1 of the present invention;
[0035] Figure 6 This is an interface morphology diagram of the transition layer in the yttria-alumina composite ceramic prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0036] The following embodiments of the technical solution of the present disclosure are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present disclosure, and are therefore only used as examples, and cannot be used to limit the protection scope of the present disclosure.
[0037] It should be noted that, unless otherwise specified, the technical terms or scientific terms used in this application should have the common meanings understood by those skilled in the art to which the present invention belongs.
[0038] In the description of the present application, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the present invention.
[0039] In addition, the terms "first", "second", etc. are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.
[0040] In this application, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0041] In the present application, unless otherwise clearly specified and limited, a first feature being “above” or “below” a second feature may mean that the first and second features are in direct contact, or the first and second features are in indirect contact through an intermediate medium. Moreover, a first feature being “above”, “above”, and “above” a second feature may mean that the first feature is directly above or obliquely above the second feature, or simply means that the first feature is higher in level than the second feature. A first feature being “below”, “below”, and “below” a second feature may mean that the first feature is directly below or obliquely below the second feature, or simply means that the first feature is lower in level than the second feature.
[0042] A method for preparing a yttrium oxide-aluminum oxide transition layer composite ceramic is provided in Examples 1-3 of the present invention. The specific parameters of the preparation process of the yttrium oxide-aluminum oxide transition layer composite ceramic are shown in Table 1.
[0043] A method for preparing an yttria-alumina transition layer composite ceramic, comprising:
[0044] S1. Raw material selection: Alumina powder and yttrium oxide powder are used; the alumina powder is commercial alumina granulated powder with a particle size of 2-90 μm and an average particle size of 57 μm; the yttrium oxide powder is commercial yttrium oxide granulated powder with a particle size of 21-64 μm and an average particle size of 38 μm;
[0045] S2. Adding quantitative raw materials: laying a predetermined amount of alumina powder, transition mixed powder and yttrium oxide powder in the molding die of the cold isostatic press from bottom to top, forming a raw material arrangement in which the upper layer is yttrium oxide powder, the transition layer is transition mixed powder and the lower layer is alumina powder; the laying process of alumina powder, transition mixed powder and yttrium oxide powder is as follows:
[0046] S201, adding alumina powder: adding a certain amount of alumina powder to a forming mold of a cold isostatic press, and vibrating and compacting the alumina powder in the forming mold;
[0047] S202, adding transition mixed powder: the transition mixed powder is a mixture of aluminum oxide powder and yttrium oxide powder; in the transition mixed powder, the mass ratio m of aluminum oxide powder and yttrium oxide powder is (3-7): (7-3), that is, the mass ratio m of aluminum oxide powder and yttrium oxide powder is 0.429-2.333; adding the transition mixed powder to the forming mold of the cold isostatic press, and vibrating and compacting the transition mixed powder in the forming mold to form a transition layer; the thickness of the transition layer is 1 mm; the forming mold is provided with scale one and scale two near its upper and lower ends respectively, and the transition layer is located between scale one and scale two of the forming mold; Figure 1 As shown;
[0048] S203, adding yttrium oxide powder: adding a certain amount of yttrium oxide powder to a forming mold of a cold isostatic press, and vibrating and compacting the aluminum oxide powder in the forming mold;
[0049] S3, repeat step S2 n times until the raw material fills the entire molding die; wherein n ≥ 0;
[0050] S4, placing the filled molding die into a cold isostatic press for cold isostatic pressing; the cold isostatic pressing pressure is 120 MPa, and the holding time is 30 seconds to obtain a molded ceramic green body; Figure 2As shown; the powder raw materials in the forming mold are uniformly pressurized by cold isostatic pressing process, the powder raw materials are compressed in volume and the pores are discharged, so that a formed ceramic green body with uniform structure and high density can be obtained;
[0051] S5. Obtain at least one yttrium oxide-aluminum oxide transition layer composite ceramic green body by machining the formed ceramic green body, and process the yttrium oxide-aluminum oxide transition layer composite ceramic green body into a designed shape, with the alumina portion serving as the alumina substrate, the transition mixed powder serving as the transition layer, and the yttrium oxide portion serving as the coating; when n=0, the number of the yttrium oxide-aluminum oxide transition layer composite ceramic green bodies obtained is 1; when n=1, the number of the yttrium oxide-aluminum oxide transition layer composite ceramic green bodies obtained is 2; when n=2, the number of the yttrium oxide-aluminum oxide transition layer composite ceramic green bodies obtained is 3; ... when n=n, the number of the yttrium oxide-aluminum oxide transition layer composite ceramic green bodies obtained is n+1;
[0052] S6, transferring the yttrium oxide-aluminum oxide transition layer composite ceramic green body obtained in step S5 to a high-temperature sintering furnace for sintering, and naturally cooling to room temperature in the furnace to obtain the yttrium oxide-aluminum oxide transition layer composite ceramic; Figure 3 As shown, since yttrium oxide shrinks too much during the sintering process, it can be found that yttrium oxide is conical after sintering; wherein, the sintering process of the high-temperature sintering furnace includes the following steps:
[0053] S601: heating up to 300°C at a rate of 200°C / h, keeping the temperature for 2h; then heating up to 400°C at a rate of 200°C / h, keeping the temperature for 2h; then heating up to 500°C at a rate of 200°C / h, keeping the temperature for 2h; then heating up to 1650°C at a rate of 200°C / h, keeping the temperature for 2h; at 300°C to 500°C, the yttrium oxide-aluminum oxide transition layer composite ceramic green body is debonded in the furnace, i.e., the binder in the yttrium oxide granulated powder and the alumina granulated powder is decomposed and discharged;
[0054] S602: The temperature is cooled from 1650°C to 1000°C at a cooling rate of 2°C / min, and then naturally cooled to room temperature along with the furnace.
[0055] Among them, in step S2, alumina powder, transition mixed powder and yttria powder are added quantitatively respectively. The "quantitative" here refers to the amount of raw material addition designed by the technicians according to subsequent cold isostatic pressing, green body machining and sintering processes. The "quantitative" here can be adjusted by technicians according to different products. The ultimate goal is to ensure that the required yttria-alumina transition layer composite ceramics can be obtained after the green body machining and sintering processes. For example, in one embodiment, a certain amount of alumina powder is first added to the molding die of a cold isostatic press, the ratio of the added volume of the alumina powder to the volume of the inner cavity of the molding die is 1:2, and the alumina powder in the molding die is vibrated and compacted; then, a transition mixed powder is added to the molding die of the cold isostatic press, and the transition mixed powder in the molding die is vibrated and compacted, and the thickness of the transition layer formed by the transition mixed powder after vibration and compaction is 1 mm; then a certain amount of yttrium oxide powder is added to the molding die of the cold isostatic press, so that the yttrium oxide powder fills the remaining volume of the molding die, and the yttrium oxide powder in the molding die is vibrated and compacted; the filled molding die is placed in a cold isostatic press for cold isostatic pressing to obtain a molded ceramic green body; then, the molded ceramic green body is machined into a designed shape to obtain an yttrium oxide-aluminum oxide transition layer composite ceramic green body, that is, the alumina part is used as the alumina substrate, the transition mixed powder is used as the transition layer, and the yttrium oxide part is used as the coating. Of course, this implementation is only an example of obtaining one yttrium oxide-aluminum oxide composite ceramic green body. Technicians can also reasonably adjust the amount of raw material added according to the actual shape and material ratio of the product to obtain one or more yttrium oxide-aluminum oxide transition layer composite ceramic green bodies after cold isostatic pressing.
[0056] In the process of preparing yttrium oxide-aluminum oxide transition layer composite ceramics, the transition layer needs to be located between scale one and scale two of the molding mold. If the transition layer is located outside scale one and scale two on the molding mold, the amount of aluminum oxide powder added to the lower layer will be small or the amount of yttrium oxide powder added to the upper layer will be small, and a yttrium oxide-aluminum oxide transition layer composite ceramic green body cannot be machined alone. In this case, the bonding strength between yttrium oxide and aluminum oxide is cross-linked; therefore, the transition layer needs to be located between scale one and scale two of the molding mold.
[0057] Comparative Example 1
[0058] Comparative Example 1 was used as a blank control group, and its preparation process was the same as that of Examples 1-3. The difference was that no transition mixed powder was added in Comparative Example 1, that is, the transition layer described in Examples 1-3 was not added between the lower aluminum oxide powder and the upper yttrium oxide powder.
[0059] The performance test is shown in Table 1.
[0060] Test standard:
[0061] (1) Bonding Strength The bonding strength (P) between the alumina substrate and the yttrium oxide coating in the yttrium oxide-aluminum oxide transition layer composite ceramic was tested in accordance with ASTM C1583 / D4541 / D7234 / D7522, ISO 4624 / 16276-1, EN 1542 / 12004-2, and AS / NZS 1580.408.
[0062] Table 1
[0063]
[0064]
[0065] From the comparison of Examples 1-3, it can be seen that when preparing the transition mixed powder, when the mass ratio m of the aluminum oxide powder and the yttrium oxide powder is gradually adjusted from 3:7 to 1:1, the bonding strength between the aluminum oxide substrate and the yttrium oxide coating in the finally prepared yttrium oxide-aluminum oxide transition layer composite ceramic is gradually improved; when the mass ratio m of the aluminum oxide powder and the yttrium oxide powder is gradually adjusted from 1:1 to 7:3, the bonding strength between the aluminum oxide substrate and the yttrium oxide coating in the finally prepared yttrium oxide-aluminum oxide transition layer composite ceramic is gradually reduced; it shows that as m gradually increases, the bonding strength first increases and then decreases. Specifically, the yttrium oxide powder and the aluminum oxide powder are sintered at a high temperature in a certain ratio, and yttrium aluminum garnet (Y3Al5O 12 ), the relative molecular mass of yttrium oxide (Y2O3) is 225.81, and the relative molecular mass of aluminum oxide (Al2O3) is 101.96; the relative molecular mass ratio of yttrium oxide to aluminum oxide that forms yttrium aluminum garnet is: 225.81×3:101.96×5=677.43:509.8=1.3:1; therefore, when the mass ratio m of aluminum oxide powder and yttrium oxide powder is 1:1, it is closest to 1.3:1; although under the process conditions of the present technical solution, the transition mixed powder cannot form yttrium aluminum garnet crystals, the interlocking parts of the aluminum oxide particles and the yttrium oxide particles in contact will form grain boundaries, and the mechanical locking formed is tighter, and the number of interlocking points formed at this ratio is more, so the bonding force is better; when the mass ratio m is 7:3 or 3:7, the number of interlocking points of the transition mixed powder decreases, and the bonding force also decreases accordingly. Mechanical locking refers to the connection of composite materials by utilizing the bonding force formed by the surface unevenness or shape matching between two or more materials. It considers the mechanical and physical effects on the interface of two or more phases. The strength of the interface mainly depends on the number of surface locking points, that is, the surface roughness and the shear yield strength of the material.
[0066] It is worth noting that, by comparing Examples 1-3 and Comparative Example 1, it can be seen that the bonding strength of the yttrium oxide-aluminum oxide transition layer composite ceramic prepared by the present technical solution is significantly better than the bonding strength of the yttrium oxide coating prepared by the process without adding a transition mixed powder to form a transition layer, and far exceeds the bonding strength of the yttrium oxide coating prepared by the prior art (i.e., the yttrium oxide coating is prepared on an alumina substrate by a plasma spraying process, and its bonding strength is 11.7 MPa), which lays a foundation for the application of the yttrium oxide-aluminum oxide transition layer composite ceramic in the etcher as a related alumina ceramic component.
[0067] like Figure 4 As shown in FIG. 1 , the interface morphology of the yttria coating and the transition layer in the yttria-alumina transition layer composite ceramic prepared in Example 1 shows that the yttria coating and the yttria component in the transition layer are connected, and a large number of interlocking points of the alumina component appear at the interface between the yttria coating and the transition layer and in the transition layer. Figure 5 As shown in FIG. 1 , the interface morphology of the aluminum oxide substrate and the transition layer in the yttria-alumina transition layer composite ceramic prepared in Example 1 shows that there is an obvious interface between the aluminum oxide substrate and the transition layer, and the aluminum oxide substrate is connected to part of the aluminum oxide components in the transition layer. At the same time, a large number of yttria component interlocking points appear on the aluminum oxide substrate side, and part of the yttria component interlocking points on the aluminum oxide substrate side are connected to the yttria components in the transition layer. Figure 6 As shown, it is a morphology of the transition layer in the yttrium oxide-aluminum oxide transition layer composite ceramic prepared in Example 1. It can be found that the aluminum oxide component is irregularly dotted and disorderly embedded in the yttrium oxide component, and at the same time, the aluminum oxide components at different points are connected.
[0068] In summary, by setting a transition layer between the alumina substrate and the yttrium oxide coating, and the transition layer is composed of a mixture of alumina powder and yttrium oxide powder in a certain proportion, part of the alumina components in the transition layer of the prepared yttrium oxide-alumina transition layer composite ceramic are connected to the alumina substrate, and part of the yttrium oxide components in the transition layer are irregularly dotted and randomly embedded in the alumina substrate; a large amount of alumina components in the transition layer are irregularly dotted and randomly embedded in the yttrium oxide components in the transition layer, and some alumina components at different points are also connected, and the yttrium oxide components in the transition layer are connected to the yttrium oxide coating; it is precisely because of the addition of the transition layer that the yttrium oxide coating and the alumina substrate are tightly connected together through the transition layer to improve the bonding strength between the yttrium oxide coating and the alumina substrate. As shown in Table 1, the bonding strength of the yttrium oxide-aluminum oxide transition layer composite ceramic prepared in Example 1 reached 32.97 MPa, indicating that the above-mentioned interlocking phenomenon in the yttrium oxide coating, transition layer and alumina substrate effectively improved the bonding strength of the yttrium oxide-aluminum oxide composite ceramic.
[0069] The above embodiments are only used to illustrate the technical solutions of the present disclosure, rather than to limit them. Although the present disclosure has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present disclosure, and they should all be included in the scope of the claims and specification of the present disclosure.
Claims
1. A method for preparing a yttrium oxide-aluminum oxide transition layer composite ceramic, characterized in that: The steps include: S1. Raw material selection: Alumina powder and yttrium oxide powder are used; S2. Adding a certain amount of raw materials: laying a certain amount of alumina powder, transition mixed powder and yttrium oxide powder in a molding die of a cold isostatic press from bottom to top, so as to form a raw material arrangement in which an upper layer is yttrium oxide powder, a transition layer is transition mixed powder and a lower layer is alumina powder; the transition mixed powder is a mixture of alumina powder and yttrium oxide powder; S3, repeat step S2 n times until the raw material fills the entire molding die; wherein n ≥ 0; S4, placing the filled molding die into a cold isostatic press for cold isostatic pressing to obtain a molded ceramic green body; S5. Machining the formed ceramic green body to obtain at least one yttrium oxide-aluminum oxide transition layer composite ceramic green body, and machining the yttrium oxide-aluminum oxide transition layer composite ceramic green body into a designed shape, wherein the alumina portion serves as the alumina substrate, the transition mixed powder serves as the transition layer, and the yttrium oxide portion serves as the coating; S6. The yttrium oxide-aluminum oxide transition layer composite ceramic green body obtained in step S5 is transferred to a high-temperature sintering furnace for sintering, and the yttrium oxide-aluminum oxide transition layer composite ceramic is obtained after being naturally cooled to room temperature in the furnace.
2. The method for preparing the yttria-alumina transition layer composite ceramic according to claim 1, characterized in that: In step S2, the laying process of the aluminum oxide powder, the transition mixed powder and the yttrium oxide powder includes the following steps: S201, adding alumina powder: adding a certain amount of alumina powder to a forming mold of a cold isostatic press, and vibrating and compacting the alumina powder in the forming mold; S202, adding transition mixed powder: the transition mixed powder is a mixture of aluminum oxide powder and yttrium oxide powder; in the transition mixed powder, the mass ratio m of aluminum oxide powder and yttrium oxide powder is (3-7): (7-3); adding the transition mixed powder to a forming mold of a cold isostatic press, and vibrating and compacting the transition mixed powder in the forming mold to form a transition layer; S203, adding yttrium oxide powder: adding a certain amount of yttrium oxide powder into a forming mold of a cold isostatic press, and vibrating and compacting the aluminum oxide powder in the forming mold.
3. The method for preparing the yttria-alumina transition layer composite ceramic according to claim 1, characterized in that: In step S202, the molding die is provided with a first scale and a second scale near the upper and lower ends thereof, respectively, and the transition layer is located between the first scale and the second scale of the molding die.
4. The method for preparing the yttria-alumina transition layer composite ceramic according to claim 1, characterized in that: In step S202, the thickness of the transition layer is 1 mm.
5. The method for preparing the yttria-alumina transition layer composite ceramic according to claim 1, characterized in that: In step 4, the cold isostatic pressing pressure is 120 MPa and the holding time is 30 s.
6. The method for preparing the yttria-alumina transition layer composite ceramic according to claim 1, characterized in that: In step 1, the average particle size of the aluminum oxide powder is 57 μm, and the average particle size of the yttrium oxide powder is 38 μm.
7. The method for preparing the yttria-alumina transition layer composite ceramic according to claim 1, characterized in that: In step 5, when n=0, the number of yttrium oxide-aluminum oxide transition layer composite ceramic green bodies obtained is 1; when n=1, the number of yttrium oxide-aluminum oxide transition layer composite ceramic green bodies obtained is 2; when n=2, the number of yttrium oxide-aluminum oxide transition layer composite ceramic green bodies obtained is 3; ... when n=n, the number of yttrium oxide-aluminum oxide transition layer composite ceramic green bodies obtained is n+1.
8. The method for preparing the yttria-alumina transition layer composite ceramic according to claim 1, characterized in that: In step 6, the sintering process in the high temperature sintering furnace includes the following steps: S601: heating up to 300°C at a rate of 200°C / h, keeping the temperature for 2h; then heating up to 400°C at a rate of 200°C / h, keeping the temperature for 2h; then heating up to 500°C at a rate of 200°C / h, keeping the temperature for 2h; then heating up to 1650°C at a rate of 200°C / h, keeping the temperature for 2h; at 300°C to 500°C, the yttrium oxide-aluminum oxide transition layer composite ceramic green body is debonded in the furnace, i.e., the binder in the yttrium oxide granulated powder and the alumina granulated powder is decomposed and discharged; S602: The temperature is cooled from 1650°C to 1000°C at a cooling rate of 2°C / min, and then naturally cooled to room temperature along with the furnace.
9. A yttrium oxide-aluminum oxide composite ceramic prepared by the method for preparing a yttrium oxide-aluminum oxide transition layer composite ceramic according to any one of claims 1 to 8.
10. Use of the yttria-alumina composite ceramic as claimed in claim 9 as an alumina ceramic component in the inner cavity of an etcher.
Citation Information
Patent Citations
Extending lifetime of yttrium oxide as a plasma chamber material
CN101589455A
Extending lifetime of yttrium oxide as a plasma chamber material
CN102005352A
Yttrium oxide-tungsten gradient material, preparation method thereof and application of material to manufacture of alloy smelting crucible
CN106270532A
Composite load bearing board for electronic ceramics and preparation method thereof
CN112457057A
Preparation method of low-roughness yttrium oxide coating
CN117265480A
Cited By
Plasma protection composite coating with nanostructure and preparation method
CN120736898A
A plasma-etch resistant coated alumina ceramic material and method of making the same
CN122647270A